2020
DOI: 10.1080/13670050.2019.1703894
|View full text |Cite
|
Sign up to set email alerts
|

The impact of second- and third-language learning on language aptitude and working memory

Abstract: An increasing number of adults learn more than one foreign language simultaneously. While the cognitive benefits of using multiple languages from birth have been studied extensively, little is known about possible cognitive benefits of learning multiple languages simultaneously in adulthood. Among the cognitive abilities which play a role in language learning, language aptitude (LA) and working memory (WM) are argued to be crucial. Traditionally considered relatively stable, recently they are advocated to be c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…With regards to motivation, the L2 + L3 learners were found to have a significant higher motivation to learn L2 (English) than the L2 only learners (Huang et al, 2020a). The other study showed that while the L2 + L3 learners and L2 learners started with a similar working memory capacity, the former had a significantly larger capacity than the latter after one academic year (Huang et al, 2020). Therefore, the learner-based advantages among bilingual learners for L3 learning, such as learning strategies (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…With regards to motivation, the L2 + L3 learners were found to have a significant higher motivation to learn L2 (English) than the L2 only learners (Huang et al, 2020a). The other study showed that while the L2 + L3 learners and L2 learners started with a similar working memory capacity, the former had a significantly larger capacity than the latter after one academic year (Huang et al, 2020). Therefore, the learner-based advantages among bilingual learners for L3 learning, such as learning strategies (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, they are related to the student's aptitude toward language learning based on her performance in the classroom. Thus, the linguistic, (meta) cognitive, social, cultural or affective benefits obtained from learning an FL by the MID student are brought to bear on prevailing theories in the field [12][13][14][15][16][17][18][19][20][21][22][23][24]31]. Regarding these, we have perceived that the stakeholders have mainly been centered on the (meta) cognitive benefits, such as autonomy and selfdetermination, as well as the social-affective benefits, namely the self-esteem and selfconcept of the MID student.…”
Section: Discussionmentioning
confidence: 99%
“…A significant and recurrent obstacle that stands in the way is the diversity of learning profiles inherent among these students [11]. Nevertheless, the numerous benefits in the linguistic domain [12][13][14][15][16][17]; cognitive and metacognitive domains [18][19][20][21]; sociocultural domain [22][23][24]; and socioemotional dimension [25][26][27] have been reported in the literature. Furthermore, as stated in the Salamanca Agreement [28], the European Commission [29] and by other researchers [19,23,30], any student has the right to receive a good quality education and equal educational opportunities from an ethical and legal point of view.…”
Section: Introductionmentioning
confidence: 99%
“…On the day following the last training session (Day 4), participants came to the computer lab for the posttest and also took the aptitude tests later during the subsequent week. Because aptitude may improve with extensive linguistic experience (Huang et al, 2020), the aptitude measures should have been taken prior to the experimental treatment (e.g. before Week 1).…”
Section: Methodsmentioning
confidence: 99%